The Monomyth in Momoiro Clover Z's Narrative - Astera Khirana (Universitas Diponegoro, 2023)
This study explores the distinctive narrative of Momoiro Clover Z, a Japanese female idol group that defied traditional idol conventions. Central to Momoiro Clover Z's identity was their deliberate departure from the typical kawaii idol image, portraying themselves as strong women. Their narrative closely adhered to the monomyth or Hero's Journey framework, chronicling their transformation from ordinary individuals to celebrated idols. This storytelling strategy resonated deeply with fans and was pivotal to their meteoric rise. Despite having only few members and abolishing interactive events like handshakes, Momoiro Clover Z used the concept of kyara to distinguish members and engage fans. They cultivated a family-friendly image, appealing to diverse demographics while avoiding objectification and the sexualization often associated with idols. In summary, Momoiro Clover Z's success can be attributed to their unique narrative approach, differentiating them from traditional idols, and their emphasis on their journey to stardom. By incorporating elements of the monomyth framework, they solidified their identity as strong women and earned their status as one of Japan's most influential female idol groups. <a href=